2009
DOI: 10.1007/s00412-009-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

At the right place at the right time: novel CENP-A binding proteins shed light on centromere assembly

Abstract: Centromeres, the chromosomal loci that form the sites of attachment for spindle microtubules during mitosis, are identified by a unique chromatin structure generated by nucleosomes containing the histone H3 variant CENP-A. The apparent epigenetic mode of centromere inheritance across mitotic and meiotic divisions has generated much interest in how CENP-A assembly occurs and how structurally divergent centromeric nucleosomes can specify the centromere complex. Although a substantial number of proteins have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…We showed that Arabidopsis KNL2 is associated with centromeres during all stages of the cell cycle, except from metaphase to mid-anaphase, similar to Mis18 of fission yeast (Hayashi et al, 2004;Williams et al, 2009), but different to the human Mis18 complex, which is only transiently present at centromeres after mitotic exit (Fujita et al, 2007;Maddox et al, 2007;Silva and Jansen, 2009).…”
Section: The Subcellular Localization Of Arabidopsis Knl2 Is Similar mentioning
confidence: 86%
See 1 more Smart Citation
“…We showed that Arabidopsis KNL2 is associated with centromeres during all stages of the cell cycle, except from metaphase to mid-anaphase, similar to Mis18 of fission yeast (Hayashi et al, 2004;Williams et al, 2009), but different to the human Mis18 complex, which is only transiently present at centromeres after mitotic exit (Fujita et al, 2007;Maddox et al, 2007;Silva and Jansen, 2009).…”
Section: The Subcellular Localization Of Arabidopsis Knl2 Is Similar mentioning
confidence: 86%
“…C. elegans KNL2 and cenH3 colocalize at centromeres throughout the cell cycle and coordinate kinetochore assembly and chromosome segregation. Human KNL2 and other components of the human Mis18 complex are transiently present at centromeres after mitotic exit (Fujita et al, 2007;Maddox et al, 2007;Silva and Jansen, 2009). Knockout of murine Mis18a is embryo lethal (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Centromeres are ubiquitous structures, observed in plant and animal cells, involved in holding sister chromatids together, being a platform for kinetochores and ensuring proper segregation of homologous chromosomes during mitosis. 41,[43][44][45][46][47] The underlying DNA sequence is variable, comparing different species; although proximity to repetitive DNA is a frequent motif. The current view is that centromeres are epigenetic structures built around a centromere-specific highly conserved histone H3 variant CENH3, which is critical for the binding of other centromere-specific proteins and the establishment of unique nucleosomal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all three proteins show a similar temporal localization pattern: targeting to the centromere just prior to CENP-A assembly during anaphase and leaving around 2 to 3 h later, in mid G1 (Fujita et al 2007;Maddox et al 2007;Silva and Jansen 2009). Despite their critical role in CENP-A assembly, none of these proteins appear to interact directly with CENP-A (Hayashi et al 2004;Fujita et al 2007;Lagana et al 2010), suggesting an indirect role for this complex.…”
Section: Cenp-a: a Key Epigenetic Centromere Markmentioning
confidence: 87%
“…The conserved role of this histone variant and its constitutive localization at all active centromeres throughout the cell cycle make CENP-A a strong candidate for a major function in centromere specification and propagation (Allshire and Karpen 2008;Silva and Jansen 2009). Indeed, recent studies provide direct evidence that CENP-A acts as a seed that is both necessary and sufficient for the formation of a fully functional centromere (Barnhart et al 2011;Mendiburo et al 2011).…”
Section: Cenp-a: a Key Epigenetic Centromere Markmentioning
confidence: 99%